Pengaruh Stabilitas Keuangan dan Target Keuangan terhadap Kecurangan Laporan Keuangan : (Survei pada Perusahaan Food and Beverage yang Terdaftar di BEI Tahun 2018-2022) - Octavia Eriyana; Dewi Saptantinah Puji Astuti (Jurnal Riset Ekonomi dan Akuntansi, 2024)
This research aims to analyze the effect of financial stability on fraudulent financial reports in food and beverage companies and financial targets on fraudulent financial reports in food and beverage companies listed on the BEI (Indonesian Stock Exchange). This type of research uses quantitative data, secondary data sources in the form of company financial reports. The number of samples for this research was 20 companies, the sample collection technique used a purposive sampling method. The research data collection method uses documentation methods obtained from the official website www.idx.co.id and the official website of food and beverage sub-sector companies. This research is new in the year of research and research objects used. The analysis technique used is multiple regression test, t test, and coefficient of determination test using SPSS software. The research results show that financial stability has no significant effect on fraudulent financial reports in food and beverage companies, and financial targets have a significant effect on fraudulent financial reports in food and beverage companies. The limitation of this research is that it only uses two independent variables and this research uses a small sample size, namely 64 samples. Suggestions for future researchers are that they can add other independent variables that could possibly influence financial report fraud and that future researchers can choose research samples from industrial sectors other than food and beverage.